رومی‌ ،سعدی اور حافظ کے کلام میں صلح و دوستی - Dr. Ali Biyat; Dr. Aneela Saleem (Khayaban - خیابان, 2023)
In Maulana Rumi's Masnavi Manawi and Dewan Shams, where the levels of love and the places of mysticism are taught, in every poem and every story there is an expression of teaching and admonishing peace, friendship, mutual respect and good behavior among humans. Sheikh Saadi traveled all over the world and collected the lessons of love, peace, friendship, ethics, reconciliation and brotherhood from every city, country and region, and made Gulistan by gathering a great harvest of knowledge and invited polite people to visit Boostan. in Gulestan or Boostan, in both of them, they are seen in the condemnation of every evil and the praise and glorification of every good. Hafiz Shirazi's charming poetic is a rich collection of peace and friendship with each other. He himself is against color and hypocrisy and invites his addressees to be monotonous and sincere